Application of information and communication technology for internationalization of Nigerian small‐ and medium‐sized enterprises - Saheed A. Gbadegeshin; Solomon S. Oyelere; Sunday A. Olaleye; Ismaila T. Sanusi; Dandison C. Ukpabi; Olayemi Olawumi; Ayobami Adegbite (Wiley, 2022)
Information and communication technology (ICT) has fundamentally transformed business transactions. While its uses have become ubiquitous in the advanced economies, emerging and developing economies are still struggling with the mode and manner of the deployment of ICT for business. Thus, this study seeks to investigate how small‐ and medium‐sized enterprises (SMEs) utilize ICT in Nigeria for business internationalization. To achieve the goal of the study, a mixed‐method was employed. A questionnaire was administered to 265 people consisting of SMEs staff, managers, and owners. Similarly, interviews were conducted with seven SME decision makers. Findings revealed that Nigerian SMEs used ICT tools, such as websites and social media platforms, for internationalization. The findings also revealed that the challenges of ICT did not affect its application by these SMEs, which contrasts with many previous studies. Furthermore, this study identified privacy concerns, internet problems, cyber insecurity, trust, and system anxiety as new challenges facing the application of ICT tools by SMEs. Similarly, the findings showed that lack of ICT competence and strategic focus of ICT applications are internal problems facing Nigerian SMEs. These findings provide insight for practitioners and academia on the internationalization of Nigeria SMEs and the application of ICT to promote business growth.